PALEOZOIC EVOLUTION OF PRE-VARISCAN TERRANES: FROM GONDWANA TO THE VARISCAN COLLISION - Stampfli G.M.; Borel G.D.; Von Raumer J.F. (My University, 2002)
The well-known Variscan basement areas of Europe contain relic terranes with a pre-Variscan evolution testifying to their peri-Gondwanan origin (e.g., relics of Neoproterozoic volcanic arcs, and subsequent stages of accretionary wedges, backarc rifting, and spreading). The evolution of these terranes was guided by the diachronous subduction of the proto-Tethys oceanic ridge under different segments of the Gondwana margin. This subduction triggered the emplacement of magmatic bodies and the formation of backarc rifts, some of which became major oceanic realms (Rheic, paleo- Tethys). Consequently, the drifting of Avalonia was followed, after the Silurian and a short Ordovician orogenic event, by the drifting of Armorica and Alpine domains, accompanied by the opening of the paleo-Tethys. The slab rollback of the Rheic ocean is viewed as the major mechanism for the drifting of the European Variscan terranes. This, in turn, generated a large slab pull force responsible for the opening of major rift zones within the passive Eurasian margin. Therefore, the µrst Middle Devonian Variscan orogenic event is viewed as the result of a collision between terranes detached from Gondwana (grouped as the Hun superterrane) and terranes detached from Eurasia. Subsequently, the amalgamated terranes collided with Eurasia in a second Variscan orogenic event in Visean time, accompanied by large-scale lateral escape of major parts of the accreted margin. Final collision of Gondwana with Laurussia did not take place before Late Carboniferous time and was responsible for the Alleghanian orogeny.
Keywords: Paleozoic; Paleozoic; Палеозой